2013
DOI: 10.1111/jpc.12267
|View full text |Cite
|
Sign up to set email alerts
|

Review of the management of childhood asthma in Tasmania

Abstract: These results indicate gaps in childhood asthma management, in particular, undersupply of preventers in high-risk patient groups, high supply of LABAs and insufficient spacer and asthma action plan usage. These areas should be targeted for interventions to improve childhood asthma management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Some in vitro experiments have shown that repeated bronchoconstriction induces epithelial cell stress, which may eventually lead to remodeling [ 16 ]. Bereznicki et al have reported that 25.7% of children with asthma in Tasmania, Australia, are treated with LABA [ 17 ]. In the present study, we found that 32.13% of pediatric patients received LABA monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro experiments have shown that repeated bronchoconstriction induces epithelial cell stress, which may eventually lead to remodeling [ 16 ]. Bereznicki et al have reported that 25.7% of children with asthma in Tasmania, Australia, are treated with LABA [ 17 ]. In the present study, we found that 32.13% of pediatric patients received LABA monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Alleviating the significant burden of disease attributable to asthma can be achieved by optimising the control of symptoms, a long‐term goal requiring regular medical review, pharmacotherapy and carer education . Shown to play a key role in reducing the severity and duration of acute exacerbations, current guidelines also recommend the provision of an individualised asthma action plan (IAAP) for all asthmatic patients and their carers to guide self‐management efforts …”
mentioning
confidence: 99%
“…Despite internationally proven benefits, rates of IAAP uptake and compliance remain low. Recent Australian studies have reported that 47.3–53% of clinically diagnosed asthmatic children do not own a plan . For parents/carers who do own a plan for their child, rates of non‐adherence range from 30 to 70%, reflecting the complex challenge routine self‐management poses .…”
mentioning
confidence: 99%
See 2 more Smart Citations